Penilaian E-modul Menggambar Ilustrasi Desain Gaya Harajuku - Siahaan, Maria Angelina Arimbi; Zahra, E Lutfia; Prabawati, Melly (Universitas Negeri Jakarta, 2024)
ABSTRACT This research aims to determine the results of the e-module for Drawing Harajuku Style Design Illustrations e-module and produce an e-module for Drawing Harajuku Style Design Illustrations. The research method used in this research is a descriptive quantitative method with a pre-experimental one-shot case study approach. Data collection techniques use closed-open instruments, which is given to expert panelists using indicators based on aspects of good module characteristics and based on aspects of module quality elements. The results of this research show that material assessment based on aspects of good module characteristics obtained an assessment percentage of 90.07%, while media assessment based on aspects of module quality elements obtained an assessment percentage of 93.01%. Therefore, the overall assessment of the Harajuku Style Design Illustration Drawing E-module received an assessment percentage of 91.54% and categorized as